(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
The wages of employees working under reduced working hours shall be paid in full in the amount established for normal working hours. The rule stipulated in the first part of this article shall not apply to cases provided for in the second part of Article 415 of this Labor Code of the Republic of Uzbekistan, when the remuneration for the labor of persons under the age of eighteen working during the school year during their free time from school is carried out in proportion to the time worked or based on the products produced.